Contrasting P-T-t paths of basement and cover within the Búzios Orogen, SE Brazil – Tracking Ediacaran-Cambrian subduction zones - Vieira, Thayla Almeida Teixeira; Schmitt, Renata da Silva; Mendes, Julio Cezar; Moraes, Renato; Luvizotto, George Luiz [UNESP]; de Andrade Silva, Raphaela Lopes; Vinagre, Rodrigo; Medeiros, Silvia Regina de (Elsevier, 2022)
Deeply eroded collisional orogens show complex structural and inverted stratigraphic relations with juxtaposition of rock stacks from distinct crustal levels, origins and ages, hence with contrasting P-T-t paths during convergent tectonics. This paper presents petrochronological data on Paleoproterozoic (basement) and Ediacaran (cover) gneisses tectonically interleaved during the Ediacaran-Cambrian Búzios Orogeny, in southeastern Brazil. U-Pb in zircon and EPMA U-Th-Pb in monazite data, coupled with geothermobarometric data, plus Zr-in-rutile, reveal that at a first orogenic stage (ca. 530–520 Ma), these units were at distinct crustal levels. Samples within the Paleoproterozoic basement show metamorphic near-peak conditions of ∼800 °C and 10 kbar, at a depth of c.37 km. Contrastingly, Ediacaran kyanite-orthoclase-garnet-biotite granulite with retrometamorphic sillimanite (cover) reached near-peak conditions of 15 kbar and 818 °C–785 °C at depths of c. 55 km, in high-pressure granulite facies. This deep burial of Ediacaran sediments in less than 20 m.y. would be compatible with a low angle subduction zone active from ca. 550 to 530 Ma. Intrusion of ca. 550 Ma tholeiitic dykes in the Paleoproterozoic gneiss indicates a high geothermal gradient for this subduction setting, which is consistent with a low subduction rate. In a second orogenic stage (ca. 520–500 Ma), these distinct stratigraphic units were placed tectonically side by side during a fast exhumation, preserving an inverted metamorphic stack. The cover underwent retrometamorphic conditions of 800 °C and 10 kbar on a clockwise return path due to decompression. It is proposed here that the contact between reworked units within a Paleoproterozoic continental crust and Ediacaran magmatic and sedimentary units represent the suture of an Ediacaran NW-subduction of the Angola continental paleomargin below the Oriental Terrane of the Ribeira belt. This paper reports the highest pressure recorded in Ediacaran-Cambrian metamorphic rocks from the Brasiliano belts along the actual South Atlantic continental margins. The suture we propose here is aligned along strike, with a medium to high-pressure Ediacaran metamorphic occurrence 700 km to the SW, in the Curitiba Terrane.
Keywords: Cabo Frio Tectonic Domain; Geothermobarometry; Petrochronology; U-Pb zircon; U-Pb-Th monazite; Zr-in-rutile